Cardiorenal Effects of Newer NSAIDs (Celecoxib) versus Classic NSAIDs (Ibuprofen) in Patients with Arthritis - Ragia Hegazy; Mohamed Alashhab; Madiha Amin (Journal of Toxicology)
Background. Arthritis is a common condition that co-exists in the elderly population. This condition leads to frequent administration of comorbid analgesics especially non steroidal anti-inflammatory drugs (NSAIDs). Aim. To study cardiorenal toxicity of celecoxib versus ibuprofen in arthritic patients. Subjects and Methods. Seven hundred ninety-wo arthritic patients were enrolled in the study for 6 months. Three hundred ninety-six patients administered celecoxib 400 mg twice a day; 396 patients administered ibuprofen 300 mg three times a day. Effects measured included investigator-reported hypertension, edema, or congestive heart failure, increases in serum creatinine or reduction in serum creatinine clearance, and changes in serum electrolytes. Results. Celecoxib was associated with significant (P<.05) lower incidence of hypertension and edema in comparison with ibuprofen. Systolic hypertension occurred significantly less (P<.05) with celecoxib compared with ibuprofen. Serum creatinine was significantly increased (P<.05) in patients treated with ibuprofen in comparison with celecoxib. Creatinine clearance was significantly lower (P<.05) in cases treated with ibuprofen in comparison to celecoxib. Nonsignificant changes in serum body electrolytes occurred. Conclusion. The most important finding of this study was the lowering incidence of cardiorenal toxicity of celecoxib in comparison with ibuprofen.